MARRIAGE DISPENSATION WITH URGENT REASONS IN THE STUDY OF MUBADALAH AMONG URBAN MUSLIMS - Rohmadi, Rohmadi (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
Laws and regulations in Indonesia have regulated the existence of a new regulation on the marriage age limit, namely 19 years applicable to men and women, as stipulated in Law Number 16 of 2019 in response to the birth of the Constitutional Court Decision Number 22/PUUXV/2017, the marriage dispensation will be granted if two conditions are met, namely; First, it is urgent and has Second, it has sufficient evidence. This rule often makes it difficult for the community, so finally, many efforts to dispense Marriage are carried out to be able to carry out marriage contracts formally among urban Muslims. The problem is how the judge's efforts in responding to the application for marriage dispensation for children far from the minimum age limit of Marriage, which is 19 years for men and women, and what is their contribution to efforts to reform the marriage law in Indonesia? This research aims to contribute new thinking to the reform of marriage law scientifically and logically. This research is a type of literature research, with a scientific-ratio approach to the minimum age limit for Marriage in Law Number 16 of 2019, with the theory of sadd al-dzariah as an effort to be able to present legal justice. The conclusion is that the determination of the judge of the Religious Court regarding the dispensation of Marriage for urgent reasons is the main argument, so there are often decisions on marriage dispensation at the age of under 16 years. However, according to the evidence submitted, sadd al-dzariah is a solution that logically violates the scientific ratio rules.